Development and validation of a risk stratification model for immediate microvascular breast reconstruction. Issue 7 (28th September 2019) - Roy, Mélissa; Sebastiampillai, Stephanie; Haykal, Siba; Zhong, Toni; Hofer, Stefan O. P.; O'Neill, Anne C.
Abstract: Background: Immediate breast reconstruction has many advantages but is associated with higher complication rates than delayed reconstruction. Complications can delay the delivery of adjuvant cancer treatments. This study aimed to develop and validate a risk stratification model for the prediction of perioperative complications in immediate microvascular breast reconstruction. Methods: The association between patient and treatment variables and perioperative complications was evaluated in a retrospective cohort of 351 women undergoing immediate breast reconstruction using free deep inferior epigastric artery perforator flaps. Multivariable logistic regression was used to determine the strength of association and weighted scores were assigned. Using cumulative risk scores, patients were stratified into low, intermediate, and high‐risk groups. The model was then validated in a prospective cohort of 100 consecutive patients. Results: Obesity, smoking, prior radiation, and comorbidities were important predictors and incorporated into the risk model. Complications occurred in 23.5% of low‐risk (95% confidence interval [CI] = 17.7‐29.2), 38.4% of intermediate‐risk (95% CI = 29.2‐47.5) and 53.9% of high‐risk (95% CI = 33.3‐74.4) patients. Validation confirmed a linear relationship between the risk stratification categories and complications in a model with good predictive power (c‐statistic = 0.7, 95% CI = 0.6‐0.8). Conclusion: A simple risk score, based on known preoperative variables, provides accurate risk stratification for patients considering immediate microvascular breast reconstruction.